2021
DOI: 10.1111/gcb.15904
|View full text |Cite
|
Sign up to set email alerts
|

Remoteness does not enhance coral reef resilience

Abstract: Remote coral reefs are thought to be more resilient to climate change due to their isolation from local stressors like fishing and pollution. We tested this hypothesis by measuring the relationship between local human influence and coral community resilience. Surprisingly, we found no relationship between human influence and resistance to disturbance and some evidence that areas with greater human development may recover from disturbance faster than their more isolated counterparts. Our results suggest remote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 73 publications
5
19
0
Order By: Relevance
“…If rural areas are more difficult to regulate, or last in line for infrastructural improvements, they may drive a higher toxic load on reefs from facilities like leaking cesspools/ underground storage tanks (Yoshioka et al, 2016;Abaya et al, 2018). Finally, our results align with a recent meta-analysis on bleaching susceptibility in human-dominated and isolated reefs (e.g., atolls), which provide limited evidence for "remote refugia" but indicate some resilience in human-dominated habitats (Baumann et al, 2022). In particular, our results suggest that regions that are not yet developed but show symptoms of new development (non-urban turbidity) may be particularly susceptible to coral bleaching.…”
Section: Discussionsupporting
confidence: 85%
“…If rural areas are more difficult to regulate, or last in line for infrastructural improvements, they may drive a higher toxic load on reefs from facilities like leaking cesspools/ underground storage tanks (Yoshioka et al, 2016;Abaya et al, 2018). Finally, our results align with a recent meta-analysis on bleaching susceptibility in human-dominated and isolated reefs (e.g., atolls), which provide limited evidence for "remote refugia" but indicate some resilience in human-dominated habitats (Baumann et al, 2022). In particular, our results suggest that regions that are not yet developed but show symptoms of new development (non-urban turbidity) may be particularly susceptible to coral bleaching.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, when a disturbance event occurs (e.g., marine heatwave), the impact of coral bleaching is far more prevalent. Alternatively, the antagonistic relationship may exist because the impacts of global warming eclipse the impacts of local stressors (Baumann et al., 2022; Bruno et al., 2019; Bruno & Valdivia, 2016; Hughes et al., 2017). Our results also show regional variation affects the response of coral bleaching to local stressors, both independently and under thermal stress (Figure 3, Supporting Information Figures S5 and S6).…”
Section: Discussionmentioning
confidence: 99%
“…The distance of 50 km was selected after preliminary analyses showed negligible differences in model performance between 25, 50 and 100 km distance (Supporting Information Table S1). Therefore, the 50‐km distance was used as it represents a regularly used distance for studies investigating human impacts associated with coral reefs (Bruno & Valdivia, 2016; Moberg & Folke, 1999; Mora, 2008), and was found to consistently provide the best fit for models in studies where multiple other distances ranging from 10–500 km were used (Alves et al., 2022; Baumann et al., 2022). HPD represents a proxy of the implied impacts of local scale stressors (Bruno et al., 2019; Cinner et al., 2013; D’agata et al., 2014; Mora, 2008; Nyström et al., 2000; Williams et al., 2008) that have potential to exacerbate coral bleaching.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a study in one of Indonesia’s oldest marine parks during the same heatwave found that management zone made no difference to coral losses ( 62 ). More recently, Baumann et al’s ( 63 ) global meta-analysis tested the relationship between human influence and coral resilience and concluded that reefs isolated from human pressures are not more resilient to climate change, noting that even the world’s most remote reefs bear the impacts of intense marine heatwaves. We concur that at broad spatial scales, exposure to thermal stress will be highly variable across the considered reefs, and this may well be the primary determinant of reef impacts; remote reefs are not immune to high thermal stress exposure levels.…”
Section: Discussionmentioning
confidence: 99%